Distributed compressed sensing multi-target positioning method based on wavelet transform. (25th January 2021) - Zhang, Yuangang; He, Fangyuan; Liu, Zhenzhen; Wang, Xuqi; Wang, Wei
In the environment of coal mine underground tunnel, it is difficult to establish a unified electromagnetic propagation model because of the factors that multi-path effect and electromagnetic wave propagation loss are numerous and complicated, in addition, the trilateral positioning of electromagnetic wave ranging is very demanding on the hardware system. In order to solve the problems, a multi-target positioning method of distributed compressed sensing based on wavelet transform is proposed, which is on the basis of researching the low power consumption and lightweight design of underground tunnel hardware. The method makes full use of the spatial correlation information of the nodes in the tunnel and transforms the target positioning problem into a joint recovery problem of signal group data. The target positions can be achieved through a non-cooperative manner and a small number of sample values, which effectively reduces the additional energy consumption caused by the exchange of data between nodes. The simulation results show that the proposed method satisfies the application of underground hardware nodes in an energy efficient way.